The quantity and quality of industrial wastewater from laundry on example of "fliegel textilservice" company in Nowe Czarnowo = Ilość i jakość ścieków przemysłowych popralniczych na przykładzie pralni Fliegel Textilservice w Nowym Czarnowie - Bering, Sławomira; Mazur, Jacek; Tarnowski, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The quality and quantity data of industrial laundry wastewater from the Fliegel Textilservice laundry in Nowe Czarnowo in West Pomeranian Voivodship are presented. The output data for analysis were measurements of pollution indicators? concentrations made for mechanically pre-treated raw wastewater in the period from 12.2009. to 07.2010.
Keywords: ilość i jakość ścieków; ścieki popralnicze; quantity and quality of sewage; industrial-laundry sewage